Cross-Linked Methyl Cellulose Films with Murta Fruit Extract for Antioxidant and Antimicrobial Active Food Packaging - Guarda-Moraga, A; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A (Elsevier B.V., 2016)
The use of biopolymers as substitutes for non-degradable traditional plastics is an interesting alternative particularly for short-term applications, such as food packaging. Additionally, active packaging has attracted much attention as an innovative technology for food conservation. Thus, the functionality of biocomposite films based on methyl cellulose (MC) and murta fruit (MU) (Ugni molinae Turcz) extract was studied. Murta fruit is a native Chilean berry and good source of antioxidant and antimicrobial compounds. First, a MU extract with the highest antioxidant ability and polyphenolic content was selected, and active MC films were prepared by casting using glutaraldehyde (GA) to improve their water resistance. The effects of GA concentration and incorporation of MU extract on material properties and antimicrobial and antioxidant activities were examined. The addition of GA greatly decreased swelling index, improved mechanical properties and antioxidant and antimicrobial activities achieved highest potential when GA was added at lowest concentration. © 2016 Elsevier Ltd.